Magnetic field due to a finite current carrying disk considering a vari able current density along its radial dimension - Díaz Florez, Guillermo A. (2013)
This paper proposes a fast and accurate methodology to calculate the magnetic field produced by a finite disk considering a linear variation of the current density between the inner and the outer radius. The mathematical expressions have been developed with the aim of reducing the computational effort, while ensuring accurate and reliable results. Additionally, the strategies presented in this work provide expressions which are free of singularities.